The Constructions of Egg-Shaped Surface Equations using Hugelschaffer’s Egg-Shaped Curve - Ahmat Rif’an Maulana; Mahmud Yunus; Dwi Ratna Sulistyaningrum (Indonesian Journal of Physics, 2015)
Hugelschaffer’s egg-shaped curve is egg-shaped curve that is constructed by two non-concentric circles using Newton’s transformation known as hyperbolism. This study has goals to construct the egg-shaped surface equations using Hugelschafer’s egg-shaped curve that is rotated on x-axis, y-axis and z-axis; to get the volume formula of the egg-shaped solid and the egg-shaped surface area and also to visualize the egg-shaped surface equations using GeoGebra. Hugelschaffer’s egg-shaped curve is selected because its equation is simple. The procedures of the construction of the egg-shaped surface equations are done by drawing the curve on xy-plane and xz-plane, then it is rotated on axes of the coordinate. Whereas, the volume formula of the egg-shaped solid is gotten by using the disk method of the volume integral. The egg-shaped surface area is attained by using the integral of surface area. Visualisation of the egg-shaped surface equations are done by choosing vary of parameter values of the equations that aims to know the effect of the parameter values with the shaped surface.